2018
DOI: 10.1016/j.immuni.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Analysis of Bone Marrow Neutrophils Reveals Populations Specialized in Expansion, Trafficking, and Effector Functions

Abstract: Neutrophils are specialized innate cells that require constant replenishment from proliferative bone marrow (BM) precursors as a result of their short half-life. Although it is established that neutrophils are derived from the granulocyte-macrophage progenitor (GMP), the differentiation pathways from GMP to functional mature neutrophils are poorly defined. Using mass cytometry (CyTOF) and cell-cycle-based analysis, we identified three neutrophil subsets within the BM: a committed proliferative neutrophil precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
680
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(741 citation statements)
references
References 55 publications
56
680
5
Order By: Relevance
“…4A). This observation is also in accordance with a recently published study (18), where the authors reported decreased Ly-6G surface expression on proliferating neutrophils. Modeling the time-series by following the trajectory along the first principal component axis of the density distribution reveals two major peaks of differentiating populations.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…4A). This observation is also in accordance with a recently published study (18), where the authors reported decreased Ly-6G surface expression on proliferating neutrophils. Modeling the time-series by following the trajectory along the first principal component axis of the density distribution reveals two major peaks of differentiating populations.…”
Section: Resultssupporting
confidence: 93%
“…In a recent study, Evrard et al . used in vivo administration of IdU to phenotypically and functionally distinguish proliferating and non-proliferating populations of immune cells (18). Here, we built on these two papers to perform IdU pulse-chase in live animals over multiple time points and to address the dynamics of differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is primarily due to the earlier expression of CD11b, compared to the differentiation in rhesus macaques. Interestingly, in mice CD11b and CD32 are expressed on the cell surface throughout the entire granulopoiesis (31). While metamyelocytes can be found in populations I, II, and IIIa (Figure 3 L), the majority of them (63.5±3%) display III phenotype (Figure 3 M).…”
Section: Resultsmentioning
confidence: 99%
“…Some recent studies have characterised these cells. A study of bone marrow neutrophils in mice using advanced cell cytometric techniques identified a dedicated pre-neutrophil population capable of differentiating into mature and immature neutrophils (based on CXCR2 status) [26]. This pre-neutrophil responded to systemic stressors of inflammation and malignancy by proliferating and providing a sustained neutrophil response in blood and tissues.…”
Section: Neutrophil Heterogeneity – Not All Neutrophils Are Equalmentioning
confidence: 99%